Pattern of Lower Urinary Tract Symptoms (LUTS) and satisfaction among patients having diagnostic cystoscopy - Pradhan, Tarun; Deo, Amit; Mahato, Raj Deb; Basnet, Tulasa (Nepal Journal of Obstetrics and Gynaecology, 2021)
Aims: To study the pattern of LUTS during diagnostic cystoscopy and to evaluate patient’s satisfaction using rigid cystoscopy with intra-urethral lignocaine gel. Methods: Hospital based cross-sectional observational study done in all patients attending Department of Obstetrics and Gynecology with LUTS. Diagnostic cystoscopy was performed after using intra-urethral lignocaine gel. Patients profile and indications for cystoscopy were recorded; and VAS (Visual Analogue Scale) was used to assess procedure related pain. Data stored in MS Excel and descriptive analysis performed using SPSS 21. Result: Forty-three patients were included in the study. The mean age of presentation was 45.77 years. Majority of the patients were pre-menstrual and with symptoms less than 5 year duration. Twenty-seven (62.8%) patients had urgency as indication for cystoscopy followed by cystitis and recurrent urinary infection each (16.3%). Only 2 patients had mixed urinary incontinence. Thirty- one (72.1%) had mild discomfort, seven (18.7%) moderate and 5(9.2%)severe in visual analogue scale. Conclusions: Urgency was found to be a frequent indication for diagnostic cystoscopy and use of rigid cystoscope using inra-urethral gel showed only mild discomfort to majority of patients.